2002
DOI: 10.1097/00024720-200208000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal Artery Pseudoaneurysm, a Rare Cause of Sciatic Pain

Abstract: This article describes a very unusual case of sciatic pain and motor dysfunction resulting from gluteal artery pseudoaneurysm. A 36-year-old woman with primary infertility sustained an iatrogenic injury to her left gluteal artery during transvaginal ultrasound-guided follicle aspiration. Twenty-five days after the procedure she developed severe left sciatic pain and motor dysfunction. Pelvic computed tomography and magnetic resonance imaging revealed a huge pelvic hematoma. Angiography demonstrated a gluteal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Two cases of gluteal artery pseudo aneurysm with sciatic nerve compression have been reported following transvaginal ultrasound-guided follicle aspiration for primary infertility [173] and transvaginal needle biopsy for endometriosis [132].…”
Section: Sciatica Secondary To Iatrogenic Traumamentioning
confidence: 99%
“…Two cases of gluteal artery pseudo aneurysm with sciatic nerve compression have been reported following transvaginal ultrasound-guided follicle aspiration for primary infertility [173] and transvaginal needle biopsy for endometriosis [132].…”
Section: Sciatica Secondary To Iatrogenic Traumamentioning
confidence: 99%
“…Two articles report false aneurysm of the gluteal artery that developed after harvesting of a posterior iliac crest bone graft and one article described a gluteal artery pseudoaneurysm after bone marrow biopsy. 2 To date, nine cases of gluteal artery pseudoaneurysm involving sciatic pain have been reported.…”
Section: Reported Literaturementioning
confidence: 99%
“…The pseudoaneurysm was treated successfully with percutaneous embolization; however, the patient remained significantly impaired with persistent painless foot drop. 5 Yurtseven et al 2 in 2002 reported a case of a 36-yearold woman with primary infertility who underwent a transvaginal ultrasound-guided needle follicle aspiration. Twenty-five days after the procedure, she developed severe left sciatic pain.…”
Section: Reported Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Unilateral lumbosacral plexus compression has been exceptionally described in aneurysms of the common iliac artery [6] and of the internal iliac artery [4], in a pseudo-aneurysm following renal transplantation [8], and in a few more cases involving the internal iliac [2,5] or gluteal arteries [10].…”
mentioning
confidence: 99%